DIFFERENTIATION OF MUNICIPALITIES AND THE INFLUENCE OF FLAGSHIP ENTERPRISES ON THE LEVEL OF THEIR SOCIO-ECONOMIC DEVELOPMENT - N. O. Chistyakova; I. S. Antonova; V. V. Tatarnikova; S. N. Popova (Вестник университета)
The article studies the impact of flagship enterprises on the level of socio-economic development of territories, the inflow of human capital and the intensification of entrepreneurial activity on the example of municipalities of three  subjects of the Siberian Federal district by constructing a regression model. The paper reveals the significant level  of differentiation of socio-economic development indicators for municipalities located within the same region. The  study determines the high influence of the growth of the population incomes in the absence of a significant increase in the population on the aggregate indicator of territorial development, the gross municipal product in  municipalities with flagship enterprises. The authors have identified the average impact of the flagship enterprises, in terms of stimulating the development of entrepreneurial activity, as well as revenue growth of companies  operating in these enterprises.